Fiscal equalisation and the induced under-taxation of economic rent - Petchey, Jeffrey (Curtin Unviersity, 2016)
The point of this paper is to show that under a certain set of highly plausible circumstances, the well-known fiscal equalisation transfer required to establish spa- tial efficiency in federations, regional unions of states (such as the EU) or unitary countries with local governments, induces under-taxation of economic rents. The circumstances which lead to this result are carefully explained in the paper. It is also noted that the result does not invalidate the standard spatial efficiency case for inter-regional transfers. Rather, it means that whether such transfers are wel- fare enhancing in net terms depends on the benefit from achieving spatial efficiency relative to the cost arising from the under-taxation of rent.